POLA INTERAKSI ORANG TUA DAN MAHASISWA RANTAU DI ERA DIGITAL - Alifia; Hasbi; Rahmat Muhammad (Halu Oleo University, 2025)
This study aims to analyse the impact of digital technology on the interaction patterns between parents and out-of-town students in Makassar and to analyse family interaction patterns in overcoming barriers to communication between parents and out-of-town students in Makassar. This research employs a qualitative case study strategy with a descriptive approach to depict existing facts through in-depth interviews with 5 out-of-town students and 3 parents. The results of the study show that the impact of digital technology on interaction patterns between parents and out-of-town students in the digital era includes ease and intensity in interacting using main social media platforms such as WhatsApp and other social media platforms like Instagram, along with changes in communication patterns. 2) Barriers that emerged include weak signal issues, misunderstandings, and smartphone malfunctions. 3) Solutions to these issues include students seeking stronger signal spots elsewhere or using cellular data, and resolving misunderstandings by re-chatting or switching to video calls. Digital interaction is not only practical but also plays a role in strengthening affection, supervision, and emotional support functions within the family. Sociologically, this phenomenon reflects the emergence of a new communication culture within the family that is flexible, symbolic, and adaptive to the dynamics of the times. Thus, digital media plays an important role as a bridge in maintaining family closeness amid the physical and social challenges faced by out-of-town students and their parents.